The effect of laser (384 nm) irradiation of the Lewis lung carcinoma on the tumor volume and the formation of metastases - Kanevskyi, V.A.; Osinskyi, S.P.; Pushkarev, V.M. (Доповіді НАН України, 2017)
We study the effect of laser irradiation upon implanted Lewis carcinoma. The irradiation of mice with Lewis carcinoma by a femtosecond pulsed laser with a wavelength of 384 nm was performed. Four groups of animals with different irradiation schemes were used in the experiments. The tumor volume and the number of lung metastases were detetermined. The activity of matrix metalloproteinases MMP-2 and MMP-9 in the primary tumor tissue was studied using zymography in polyacrylamide gel. The significant inhibition of the primary tumor growth and a decrease in the number of lung metastases were showed. A significant decrease of the MMP-9 level in the tumor was also observed. The most promising is the irradiation of mice with Lewis carcinoma on the 18th day after cells inoculation. There was а significant (more than 2-fold) reduction in the tumor volume, number of metastases in lungs, and MMP-9 level. Laser irradiation with a wavelength of 384 nm may be promising for the treatment of superficial tumors.